Análise da relaç\~ao entre créditos do Pronaf e diversificaç\~ao da produç\~ao agrícola em estabelecimentos de agricultura familiar no Brasil (2006-2017) - Fabio Alves; Sandro Pereira Silva; Alexandre Arbex Valadares; Lillian Bastian (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
– This study aims to analyze the relationship between credits contracted from the National Program for Strengthening Family Agriculture (Pronaf) and agricultural productive diversification in Brazilian territory. This verification took place both in terms of the percentage share of the main agricultural crops in municipalities with different levels of credits contracted from Pronaf, and in terms of the impact of these credits on a synthetic index of productive diversification. The starting point was the premise that Pronaf's operational design influences the potential for productive diversification of Brazilian family farming insofar as it limits the production decisions of its applicants. The data indicate that the program has maintained, in general terms. the tendency to follow the productive structure of local agriculture, reinforcing pre-defined dynamics. This finding is in line with the hypothesis raised about the limitation of the operational design in printing different dynamics of agricultural production.
10419/284871
Keywords: R58; J38; Q19; 330; family farming; productive diversification; public policy; Pronaf; financial logic